Adherence Predictors in Internet-Delivered Self-Help Intervention for Life Stressors-Related Adjustment Disorder - Kazlauskas, Evaldas; Eimontas, Jonas; Olff, Miranda; Zelviene, Paulina; Andersson, Gerhard (Frontiers in Psychiatry, 2020)
Background: There is a growing body of evidence that low-intensity self-help internet-delivered interventions are effective in the treatment of mental disorders. Despite promising effectiveness of internet-delivered interventions, there is still a challenge for mental health services to implement internet-delivered interventions in routine health care. The aim of this study was to analyze the predictors of adherence to a self-help internet-delivered intervention for adjustment disorder. Methods: This was a secondary report of data, including unpublished data, from a randomized controlled trial of an internet-delivered self-help intervention for adjustment disorder. The study included 1077 participants who had completed online baseline assessments. All participants experienced significant life-stressors over the last two years and had high levels of adjustment disorder symptoms. We analyzed the role of sociodemographic variables, pre-treatment adjustment disorder symptoms, outcome expectations, and perceived barriers to mental health services on the use of the intervention. Results: We found that usage of the internet-delivered self-help intervention and higher adherence was associated with female gender, greater age, higher pre-intervention outcome expectations, exposure to other forms of psychological therapy in addition to the internet-intervention at the time of the study, and reported perceived barriers to mental health services by the study participants. Conclusions: The findings of the study indicated the importance of non-specific therapeutic factors on adherence in the internet-delivered intervention. Perceived barriers to mental health services were associated with higher adherence to self-help intervention which indicates that communities with restricted access to mental health services could benefit from low-intensity internet-delivered interventions.